RETRACTED: Specifics of infrastructure construction under the conditions of urban - Sukhinin Sergey; Zilberova Inna; Novoselova Irina; Petrov Konstantin; Borovoy Vladimir (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001